2013
DOI: 10.3390/ijms14046903
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of the RESMENA Dietary Pattern on Oxidative Stress in Patients Suffering from Metabolic Syndrome with Hyperglycemia Are Associated to Dietary TAC and Fruit Consumption

Abstract: Hyperglycemia and oxidative stress are conditions directly related to the metabolic syndrome (MetS), whose prevalence is increasing worldwide. This study aimed to evaluate the effectiveness of a new weight-loss dietary pattern on improving the oxidative stress status on patients suffering MetS with hyperglycemia. Seventy-nine volunteers were randomly assigned to two low-calorie diets (−30% Energy): the control diet based on the American Health Association criteria and the RESMENA diet based on a different macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 61 publications
(65 reference statements)
0
25
0
1
Order By: Relevance
“…Anthropometric variables (weight, waist and hip circumference), body composition (total fat mass, truncal fat mass and bone mineral concentration-BMC) and blood pressure (systolic and diastolic blood pressure) measurements were carried out at baseline and at the end of the dietary intervention following validated procedures as described elsewhere [17]. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were taken in triplicate with an automatic device (Intelli Sense.…”
Section: Anthropometry Body Composition and Blood Pressurementioning
confidence: 99%
“…Anthropometric variables (weight, waist and hip circumference), body composition (total fat mass, truncal fat mass and bone mineral concentration-BMC) and blood pressure (systolic and diastolic blood pressure) measurements were carried out at baseline and at the end of the dietary intervention following validated procedures as described elsewhere [17]. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were taken in triplicate with an automatic device (Intelli Sense.…”
Section: Anthropometry Body Composition and Blood Pressurementioning
confidence: 99%
“…Briefly, the study lasted six months in two sequential periods: one intervention period of two months (-30% energy restriction, 40-55%E carbohydrate/30%E lipids/15-30%E protein) in which subjects were randomly assigned to two energy-restricted diets (control diet and RESMENA diet) followed by a self-control period of four months in which subjects were advised to follow the learned-habits in the first period, which is further described elsewhere [36,37]. Four months (week 24; T2) upon completion of the dietary intervention (week 8; T1), subjects returned to the clinical research unit for further assessment.…”
mentioning
confidence: 99%
“…The additional 73 participants (cohort 2; 42 men/31 women) followed a therapy program based on the RESMENA-S (MEtabolic Syndrome REduction in Navarra) study, which was a randomized controlled intervention trial aiming to improve clinical criteria and biomarkers associated with metabolic syndrome (Met Synd) through a dietary strategy for weight loss during six months [36,37]. Briefly, the study lasted six months in two sequential periods: one intervention period of two months (-30% energy restriction, 40-55%E carbohydrate/30%E lipids/15-30%E protein) in which subjects were randomly assigned to two energy-restricted diets (control diet and RESMENA diet) followed by a self-control period of four months in which subjects were advised to follow the learned-habits in the first period, which is further described elsewhere [36,37].…”
mentioning
confidence: 99%
“…In the Tehran Lipid and Glucose Study it was demonstrated that a high TAC has beneficial effects on metabolic disorders and especially prevents weight and abdominal fat gain [61]. In the same line, research conducted in our institutions also evidenced that beneficial effects on body weight, oxidative stress biomarkers and other MetS features were positively related with higher TAC consumption in patients suffering from MetS [63,64,65]. …”
Section: Dietary Patternsmentioning
confidence: 81%